Assessment of gender differences in secondary school achievement among Moroccan students - Hilali, Abdelkrim; Zanzoun, Mustapha; Dahmoun, Mohamed; Alami, Abderrazak El (American Journal of Education and Learning, 2023)
In Morocco, as in many other countries of North Africa and Middle East, access to education has improved during the last few decades, and gender gaps in secondary school enrolment have already disappeared. In addition, there is increasing evidence that girls have been outperforming boys in education during the last decade. The aim of this study was to assess the gender differences in three Moroccan high schools. Data was collected, in August-October 2022, from the results of 2022 Morocco’s Baccalaureate exam which refers to the secondary school graduation examinations. We have analyzed the general baccalaureate grades of all students from three establishments. The sample of three options (experimental sciences, literature and Human sciences, and mathematic) was categorized by gender into male and female. To assess the gender difference, a Mann–Whitney test was used. Results have showed that there was an increase in the number of girls compared to boys at the three studied high schools, and that girls have proved to outperform boys in the two options of experimental sciences as well as in literature and human sciences streams. On the contrary, although the number of boys exceeds that of girls for the mathematics option, they both score identical results in the subject. This difference between male and female students, which favors girls over boys, has been discussed in the light of numerous scientific studies.